1988
DOI: 10.3109/08941938809141092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Portal Vein Ligation on Hepatic Regeneration

Abstract: To evaluate the effect of portal hypertension and diminished portal venous blood flow to the liver on hepatic regeneration, male rats were subjected to partial portal vein ligation and subsequently to a two-thirds partial hepatectomy. The levels of ornithine decarboxylase activity at 6 h after partial hepatectomy were greater (p < 0.001) in the rats with prior partial portal vein ligation than in those without portal hypertension. The rats with prior partial portal vein ligation also had greater (p < 0.005) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Hepatocyte proliferation has been described when the liver is placed under stress [10], and ligation of portal vein branches was reported to induce hepatocyte growth factor expression [11]. However, with the increase in hepatocyte proliferation, we did not observe an increase in liver weight.…”
Section: Discussioncontrasting
confidence: 47%
“…Hepatocyte proliferation has been described when the liver is placed under stress [10], and ligation of portal vein branches was reported to induce hepatocyte growth factor expression [11]. However, with the increase in hepatocyte proliferation, we did not observe an increase in liver weight.…”
Section: Discussioncontrasting
confidence: 47%
“…This observation has also been demonstrated in our rodent models (personal unpublished data). Kahn et al [3] showed that rats with portal hypertension and diminished portal blood flow had a normal capacity to regenerate hepatic mass after hepatic resection. Uemura et al [4] also reported that after partial portal vein ligation, DNA synthesis in rats was significantly increased in the nonligated as compared with the ligated hepatic lobe.…”
Section: Discussionmentioning
confidence: 98%
“…Khan et al [54] studied the effects of partial portal vein ligation 8 weeks prior to hepatectomy on a murine model of partial hepatectomy. They observed that partial portal vein ligation prior to hepatectomy did not impair hepatic regeneration capacity, compared to sham animals.…”
Section: Portal Flow Modulation In Donorsmentioning
confidence: 99%